An Overview of the Clinical Characteristics of Japanese Patients with Spinal Muscular Atrophy: Data from SMART Consortium - Tamaki Kato (Society of Tokyo Women's Medical University, 2021)
Background: Patient registries play an important role in rare disease, particularly for recruitment of clinical trials and clinical research.Methods: In 2012, we launched a registry for the purpose of clarifying the clinical characteristics of spinal muscular atrophy (SMA) in Japan and with the goal of enrolling patients with SMA into newly started clinical trials. In order to document the current status of SMA in Japan, we conducted a survey based on the data of 277 SMA patients enrolled in the registry from October 2012 to July 2020.Results: Genetic testing was performed in 95% of patients. Patients with type III SMA experienced the longest onset to genetic diagnosis times, while those with type I had the shortest times. Tongue fasciculation was more common in types I and II SMA, while finger fasciculation was more common in types II and III. The site of fasciculation was thought to be the key to predicting the disease type. Over-the-counter or investigational drugs were administered to 76% of patients as of June 2019.Conclusion: Our registry is useful for understanding the current status of SMA patients in Japan, and can provide accurate and up-to-date information on the clinical course of patients over their lifetime.